Secondary osteoporosis - Sheu, Angela (Aust Prescr, 2016)
Secondary osteoporosis is less common than primary osteoporosis. It may be suspected in patients who present with a fragility fracture despite having no risk factors for osteoporosis. In addition, secondary osteoporosis should be considered if the bone density Z-score is –2.5 or less. Consider the fracture site and presence of other clinical clues to guide investigations for an underlying cause. The tests to use are those that are indicated for the suspected cause. Baseline investigations include tests for bone and mineral metabolism (calcium, phosphate, alkaline phosphatase, 25-hydroxyvitamin D, parathyroid hormone), liver and kidney function, full blood count and thyroid-stimulating hormone. More detailed testing may be required in patients with severe osteoporosis.